Process mining-based medical program evolution. (May 2018) - Cao, Yongzhong; Zhu, Junwu; Guo, Yalu; Shi, Chen
Abstract: Medical path of disease varies due to the changes in external factors, and the key to the changes is the decision-making in symptomatic treatment by medical experts; how to make full use of historical medical data and recommend high quality treatment options to new cases under the current circumstance of data explosion, is the research focus of this paper. This paper first presents the standard for medical path based on cloud platform, going into the construction of workflow-based flow model of medical services; finally, a process mining algorithm based on medical evolution factor is given to realize the evolution of online medical program of a disease.